Sub-chronic toxicity of Garcinia atroviridis Griff Fruit's ethanol extract on Wistar rats (Ratus norvegicus) - Tiana Milanda; Asti Destilia Safrudin; Galih Samudra; Sri Adi Sumiwi; Muchtaridi Muchtaridi (Wolters Kluwer Medknow Publications, 2019)
Garcinia atroviridis Griff. (GA) is a tropical fruit that commonly used as a traditional medicine to this day. This study was conducted to determine the sub-chronic toxicity effect of GA fruits ethanol extract on body weight, clinical hematology and biochemical parameters, and organ's histopathology. This study is an experimental research by oral treatments for 90 days with completely randomized design. The treatment group consists of five classes. Each class was given the treatment with a dosage of 50 mg/kg BW, 200 mg/kg BW, 800 mg/kg BW and satellite group with 2% PGA, or 800 mg/kgBW. Based on ANOVA and advanced Tukey test results using SPSS, the hematological parameters such as mean corpuscular volume, mean corpuscular hemoglobin concentration, and white blood cell had significant differences with the control group. In the biochemical parameters, the serum glutamic-oxaloacetic transaminase values and triglycerides (in male rats), serum glutamic-pyruvic transaminase and creatinine (in female rats) had significant differences with the control group. In conclusion, GA fruits ethanol extract is safe and non toxic to body weight, clinical hematology and biochemical parameters, and histopathology of ten organs.